Exploring the influence of social and structural support on entrepreneurial intentions among South Asian Canadian immigrants - Nadeem Akhtar; Syed Mohammad Azeem; Abdullah Faisal Basiouni; Ghulam Mustafa Mir (Asian Academy of Management Journal, 2023)
The focus of this paper is on the perspectives people hold towards starting their businesses. An investigation was conducted on recent immigrants to Canada, the majority of whom were from South Asian nations. Subsequently, the SmartPLS 3.2.8 analysis tool was used to examine the collected data. According to the findings of the analysis, the perception of having structural support is a poor predictor of entrepreneurial intentions. Conversely, individual characteristics, such as self-efficacy and self-control, are significant predictors of entrepreneurial intentions. The results call into question immigration policies and regulations that select immigrants based on their potential for financial success rather than the businesses they intend to start themselves. The research suggests that if immigrants with high self-efficacy were provided support from their immigrant communities, they could more easily launch new businesses. This information can serve as a guide for immigration policymakers.